2010
DOI: 10.1016/j.marenvres.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in 16 demersal sharks from southeast Australia: Biotic and abiotic sources of variation and consumer health implications

Abstract: International audienceTotal mercury (THg) and monomethylmercury (MMHg) concentrations were determined in the tissues of demersal shark (Order Squaliformes and the Families: Scyliorhinidae, Hexanchidae) and chimaera species (Families: Chimaeridae and Rhinochimaeridae) from continental shelf and slope waters off southeast Australia, including embryos, juveniles and adults. The distribution of THg in various tissues (muscle, liver, kidney, and skin), examined in ten species, shows higher levels in the muscle tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 32 publications
7
71
1
Order By: Relevance
“…This result suggests that juvenile hammerhead sharks might metabolize and excrete Hg effectively due to the excess of Se present. Recent studies showed that other processes, such as maternal offloading, may represent another important pathway of Hg accumulation, which indicate that elasmobranchs have the capacity to offload contaminants to their young (Pethybridge et al 2010;Lyons et al 2013). In the present study, it is unlikely that Hg has been retained from maternal transfer is provoked by the changes over life stages due to growth dilution and dietary accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that juvenile hammerhead sharks might metabolize and excrete Hg effectively due to the excess of Se present. Recent studies showed that other processes, such as maternal offloading, may represent another important pathway of Hg accumulation, which indicate that elasmobranchs have the capacity to offload contaminants to their young (Pethybridge et al 2010;Lyons et al 2013). In the present study, it is unlikely that Hg has been retained from maternal transfer is provoked by the changes over life stages due to growth dilution and dietary accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…We have taken 3.4 ‰ as the mean nitrogen fractionation between 2 trophic positions (Minagawa & Wada 1984;and reviewed by Post 2002). A biplot of δ 13 C vs. δ 15 N data was used to characterize the trophic structure of the chondrichthyan assemblage and allowed us to explore dietary breadth in Centroselachus crepidater and Etmopterus baxteri using summary matrices (after that used by Vaudo & Heithaus 2011) in which the total convex hull area of the δ Speciation analysis of mercury (reported in Pethybridge et al 2010a) demonstrated that ≥91% of THg was present as methylmercury (MeHg) in the white muscle tissue of most documented shark species; and thus, THg was deemed an appropriate measure of the more toxic MeHg. Analyses of total mercury (THg) were carried out on 2 to 3 replicate samples ranging from 10 to 50 mg of dried muscle tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Upper-and mid-slope chondrichthyans that occur off southeastern Australia are known to accumulate MeHg concentrations that exceed those established by community legislation (>1 ppm; Pethybridge et al 2010a). There are concerns that consumption of these species and others harvested from the same community assemblages will affect human health.…”
Section: Introductionmentioning
confidence: 99%
“…As for marine mammals and seabirds, sharks are particularly susceptible of accumulating significant levels of trace metals in their tissues, resulting key indicators of the environmental contamination status (Marcovecchio et al 1991;Vas 1991). Previous studies have, in fact, demonstrated the ability of elasmobranch fish to accumulate high concentrations of potentially toxic elements, such as mercury and methylmercury (Pethybridge et al 2010;Storelli et al 2001, arsenic (Storelli and Marcotrigiano 2004;Storelli et al 2005;Windom et al 1973), as well as copper and zinc (Lowman et al 1966). This aspect is especially interesting for biota residing in contaminated marine areas.…”
Section: Introductionmentioning
confidence: 99%